Ibn Taymiyyah's Philosophy of Education and Its Relevance to Arabic Language Learning - Muhammad Umar Zaid Alkhindi; Kamal Yusuf (Universitas Islam Negeri Sumatera Utara Medan, 2023)
Ibn Taymiyyah is a philosopher who has made important contributions to Islamic science in several areas, including philosophy of education. Ibn Taymiyyah's philosophy of education places a strong emphasis on character development, the integration of reason and revelation, and the value of practical knowledge. The purpose of this research is to examine how Ibn Taymiyyah's philosophy of education relates to Arabic language learning. Ibn Taymiyyah's writings, including Majmu' al-Fatawa, Dar'u Ta'arud al-'Aql wa an-Naql, and As-Siyasah as-Shari'ah, as well as additional supporting material, are analyzed and interpreted using a qualitative library research strategy. To determine the main idea of its philosophy of education and investigate its applicability to Arabic language learning, the data underwent both descriptive analysis of educational philosophy. The findings of the study demonstrate that Ibn Taymiyyah's philosophical concept in education encompasses knowledge as a divine mandate, knowledge as a rational search guided by revelation, and knowledge as a means of applying Islamic values. These principles are reflected in the learning of Arabic, where language understanding is not only a means of communication, but also a medium for accessing authentic Islamic texts. In addition, Ibn Taymiyyah's approach is in line with the importance of character development and deep understanding in language learning. It is evident that the implementation of Ibn Taymiyyah's educational philosophy within the context of Arabic language acquisition can foster enhancement not only of linguistic proficiency but also of spiritual development, within the paradigm of Islamic education.